The Impact of Entrepreneurship Education, Perceived Behavior Control, and Entrepreneurial Self-Efficacy on Pre-Service Teacher Candidates’ Entrepreneurial Intention - Ananda Setiawan; Annida Hafizah; Della Sapitri (AL-ISHLAH: Jurnal Pendidikan, 2024)
The purpose of this study was to determine the role of entrepreneurship education (EE), perceived behavior control (PBC) and entrepreneurial self-efficacy (ESE) on the entrepreneurial intentions of students of the Faculty of Teacher Training and Education, Universitas Lambung Mangkurat. This study used a quantitative method with the help of SEM-PLS to determine the effect of the model under study. Research data was collected through a questionnaire via e-form, which was distributed to Universitas Lambung Mangkurat students from September to December 2022. The instrument was filled with 239 students. The participants were teacher training students at Universitas Lambung Mangkurat who were chosen through a random selection process. The study's findings demonstrated that entrepreneurship education positively influences self-control and self-efficacy. Self-discipline and belief in one's ability to succeed benefit the desire to start a business. Entrepreneurship education does not influence entrepreneurial intentions. Entrepreneurship education was found to influence entrepreneurial self-efficacy and perceived behaviour control positively. Entrepreneurial self-efficacy and perceived behaviour control positively influence entrepreneurial intentions, but entrepreneurship education does not significantly benefit entrepreneurial intents.